Why Morphology Matters for Reading and Spelling Development: A Theoretical and Empirical Perspective in Individuals With and Without Dyslexia - Ardanouy, Estelle; Quémart, Pauline (Revista de Investigación en Logopedia, 2025)
While phonology is a fundamental component of reading and spelling acquisition, broader language skills, such as morphology, also play a crucial role. At the same time, phonological deficits are widely recognized as a core characteristic of developmental dyslexia, making it difficult for individuals to segment words into phonemes and contributing to challenges in both reading and spelling. However, morphological processing is relatively preserved in this population. This article reviews studies highlighting the role of morphological units in reading and spelling during typical development and in individuals with dyslexia. Studies showing that training in morphological awareness can improve written language skills in individuals with dyslexia are also presented. Throughout the manuscript, we draw on the psycholinguistic grain size theory, which offers a valuable theoretical framework for understanding the factors that may influence the processing of morphological units when reading and spelling. Concrete examples of interventions based on morphological training for clinicians are also provided.